Moderation of directors’ education on board busyness-firm efficiency - Tan, Khar Mang; Kamarudin, Fakarudin; Bany Ariffin, Amin Noordin; Abdul Rahim, Norhuda (Emerald Publishing, 2020)
Purpose: The purpose of this paper is to enhance the understanding of the long-debated impact of board busyness within a new framework of firm efficiency in the selected developed and developing Asia–Pacific countries, by assessing the moderation of directors' education towards the relationship between board busyness and firm efficiency. The extant literature on board busyness demonstrates to a lack of clarification of the relationship between board busyness and firm efficiency. Design/methodology/approach:The sample for this paper comprises a panel data of 800 firms in a cross-country context of the selected developed and developing Asia–Pacific countries during the recent period of 2009–2015. This paper performs a non-parametric Data Envelopment Analysis to measure firm efficiency and panel regression analysis to examine the moderation of directors' education. Findings: This paper provides support for the busyness hypothesis by documenting that the busy boards are likely to reduce firm efficiency. Moreover, this paper renders support to the upper-echelons theory by demonstrating that the impact of board busyness on firm efficiency is likely to turn positive in the presence of directors' education. Practical implication: This paper highlights practical implication for managers especially in the Asia–Pacific region who seek to enhance firm efficiency, which is essential for firms in attaining the primary goal of profit maximization. Originality/value: This paper builds on the extant literature by providing a contemporary research path regarding the moderation of directors' education to explain the long-debated impact of board busyness within a new framework of firm efficiency, based on a recent and significant sample of Asia–Pacific countries.